2020
DOI: 10.1002/ana.25884
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disruption in Epilepsy: Ictal and Interictal Epileptic Activity Matter

Abstract: Objective: Disturbed sleep is common in epilepsy. The direct influence of nocturnal epileptic activity on sleep fragmentation remains poorly understood. Stereo-electroencephalography paired with polysomnography is the ideal tool to study this relationship. We investigated whether sleep-related epileptic activity is associated with sleep disruption. Methods: We visually marked sleep stages, arousals, seizures, and epileptic bursts in 36 patients with focal drugresistant epilepsy who underwent combined stereo-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…Sleep difficulties and disorders are common in epilepsy and are likely multifactorial (Grigg-Damberger and Foldvary-Schaefer, 2015 ; Freeman et al, 2020 ; Winkelman and Lecea, 2020 ). In focal, drug-resistant epilepsy, sleep fragmentation is associated with seizures as well as bursts of inter-ictal epileptiform activity (Peter-Derex et al, 2020 ). Although objective sleep alterations can be attributable to seizures, the relationship between subjective sleep quality and factors such as quality of life and psychiatric comorbidities is more complicated.…”
Section: Rigorous Practices: Confounding Factors and Recommendations For Experimental Designsmentioning
confidence: 99%
“…Sleep difficulties and disorders are common in epilepsy and are likely multifactorial (Grigg-Damberger and Foldvary-Schaefer, 2015 ; Freeman et al, 2020 ; Winkelman and Lecea, 2020 ). In focal, drug-resistant epilepsy, sleep fragmentation is associated with seizures as well as bursts of inter-ictal epileptiform activity (Peter-Derex et al, 2020 ). Although objective sleep alterations can be attributable to seizures, the relationship between subjective sleep quality and factors such as quality of life and psychiatric comorbidities is more complicated.…”
Section: Rigorous Practices: Confounding Factors and Recommendations For Experimental Designsmentioning
confidence: 99%
“…Conversely, REM sleep (particularly the phasic REM sleep microstate) has an inhibitory influence on epileptic activity potentially linked to neuronal desynchronization mediated by cholinergic neurotransmission ( Ng and Pavlova, 2013 ; Frauscher et al, 2016 ). Although very rare, epileptic seizures can nonetheless be observed during REM sleep ( Minecan et al, 2002 ; Peter-Derex et al, 2020 ). Chronobiological factors also influence the occurrence of seizures ( Karoly et al, 2021 ).…”
Section: Epileptic Seizures and Dreamsmentioning
confidence: 99%
“…On the other hand, epilepsy has a disrupting effect on sleep macro- and micro-architecture. It is associated with an increase in wake after sleep onset ( Sudbrack-Oliveira et al, 2019 ; Peter-Derex et al, 2020 ) but also with a micro-structural fragmentation of sleep, linked to both ictal and inter-ictal epileptic activity ( Malow et al, 2000 ; Peter-Derex et al, 2020 ). Recently, it has been proposed that epileptic activity might disrupt NREM sleep oscillations (slow waves, spindles, ripples) underlying sleep-related memory consolidation processes, which may have a deleterious effect on patients’ cognition ( Gelinas et al, 2016 ; Lambert et al, 2020 ; Lambert et al, 2021 ).…”
Section: Epileptic Seizures and Dreamsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of side-specific hippocampal memory function of patients with focal epilepsy, evaluated with SEEG, has reported that retention of verbal memory over 1 week was negatively correlated with hippocampal spike frequency during sleep, whereas no significant correlation was found with hippocampal interictal EA occurring when awake. 7 As highlighted by Laure Peter-Derex et al, 6 not only ictal but also interictal EA occurring in the hippocampus during sleep may impair sleep quality and possibly impact memory consolidation.…”
Section: Commentarymentioning
confidence: 99%